2011
DOI: 10.1016/j.jiph.2011.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for chronic lung impairment in patients treated for pulmonary tuberculosis

Abstract: PIAT was not associated with the duration of delay in tuberculosis diagnosis and treatment and did not significantly change during follow-up. These data demonstrate that, for many individuals, the completion of tuberculosis treatment is the beginning, not the end, of their tuberculosis illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 24 publications
3
32
1
3
Order By: Relevance
“…Patients with disease with a sympatric host-pathogen relationship were more likely to have no impairment. Previously, we showed that PIAT is more frequent and severe in certain risk groups and racial/ethnic populations and also demonstrated that PIAT could be life-long (Pasipanodya et al, 2010(Pasipanodya et al, , 2012bVecino et al, 2011). In these studies, self-reported non-Hispanic white was associated with PIAT, while various measures of socio-economic status were not.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Patients with disease with a sympatric host-pathogen relationship were more likely to have no impairment. Previously, we showed that PIAT is more frequent and severe in certain risk groups and racial/ethnic populations and also demonstrated that PIAT could be life-long (Pasipanodya et al, 2010(Pasipanodya et al, , 2012bVecino et al, 2011). In these studies, self-reported non-Hispanic white was associated with PIAT, while various measures of socio-economic status were not.…”
Section: Discussionmentioning
confidence: 87%
“…Approximately 2 million persons die annually from tuberculosis (TB) and among those that survive, at least half will experience pulmonary impairment after TB (PIAT) that can be debilitating (Pasipanodya et al, 2007(Pasipanodya et al, , 2010Vecino et al, 2011;World Health Organization, 2010). Previous studies have described host, pathogen, environmental, and lifestyle factors associated with outcomes after TB exposure, after latent Mycobacterium tuberculosis infection, or after TB disease (Blaser and Kirschner, 2007;Caws et al, 2008;Coscolla and Gagneux, 2010;Kato-Maeda et al, 2001;Malik and Godfrey-Faussett, 2005;Pasipanodya et al, 2012b;van Crevel et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Post-pulmonary tuberculosis impairment was studied after 20 weeks of tuberculosis treatment and again on, or after, treatment completion 32 . The median duration between the first and the second spirometry was 15 weeks.…”
Section: Functional Evaluation Of Sequelaementioning
confidence: 99%
“…Due to the destructive nature of TB, pulmonary TB may induce chronic lung impairment (2). Despite effective TB therapy, the healing process following resolution of active TB can lead to structural damage to the lung parenchyma and airways (3).…”
Section: Introductionmentioning
confidence: 99%